Miguel Bloombito’s Spanish Translingual Twitter Account as a Means of Overcoming Discrimination against the Hispanic population in the United States - M. Yu. Semenova (Научный диалог)
The question of the use of the Spanish translingual idiom in the Twitter account of the American satirist of Puerto Rican origin, writing under the pseudonym Miguel Bloombito, is considered. Particular attention is paid to one of the main functions of such an idiom, which is used as a way to overcome language discrimination against Latin Americans living in the United States. Separately, a comprehensive analysis of this Spanish idiom, characteristic of the speech of Puerto Rican Americans, is offered. The issue of switching and mixing codes at different levels of Spanish is of interest. The author dwells on the graphic-phonetic, wordformation and lexical levels, at which a large number of contaminated elements containing allusion and based on the play of meanings are revealed. A level-by-level classification of the elements of the Spanish idiom is proposed. Evidence is given that this idiom has sufficient system stability for the language, regularity and productivity of the models for the formation of certain units, as well as a tendency towards standardization, including outside the analyzed texts. It is proved that the Spanish translingual idiom, which appeared as a result of the contact of linguistic cultures in a multi-ethnic state, demonstrates a high degree of convergence of prototype languages, expressed through switching and mixing codes.